Soil nailing wall with vertical nails to displacement reduction: Brazilian Practice - André Querelli (Dyna, 2022)
Most of the time, geotechnical engineering interventions require solutions that necessarily aim for better use of the available space. Many slope stabilization techniques were developed following that assumption, and one of the most applied procedures in Brazil is the soil nailing reinforcement. These engineering techniques are constantly improving. Consequently, a continuous study of the design and behavior of soil nails is important. The technique of vertical nails reinforcement in soil nailing is recent in the Brazilian scenario. Nowadays, some constructors started to use them near the slope face when stabilizing huge excavations. This paper aims to verify the vertical nails’ efficiency in reducing horizontal displacements. We present three numerical modeling analyses using the finite elements method (FEM). The proposed model is a soil nailing of approximately 18m high in a homogeneous subsoil in São Paulo city. Comparing situations with and without vertical nails, as if an inclined face (slope), the results showed that adding those nails could reduce horizontal displacements.